Evaluation of oxidative stress and severity of endometriosis - Shaiesta Amreen; Pratap Kumar; Priyanka Gupta; Pragna Rao (Wolters Kluwer Medknow Publications, 2019)
Aims: The aim was to evaluate the association between oxidative stress with the severity of endometriosis in blood and peritoneal fluid. Settings and Design: This study was a prospective observational study conducted in the department of obstetrics and gynecology in a tertiary center over 2 years in patients with endometriosis requiring laparoscopy. Methodology: Patients diagnosed with endometriosis and undergoing laparoscopy for infertility and/or chronic pelvic pain were included in the study. Out of the 64 patients recruited, only 55 patients formed the part of our study. Blood and peritoneal fluid was evaluated for oxidative stress parameters such as glutathione peroxidase, superoxide dismutase (SOD), and lipid peroxides. Results: The severity of endometriosis was assessed intraoperatively by the revised American Society for Reproductive Medicine scoring in all 55 patients who underwent laparoscopy into minimal (n = 3), mild (n = 7), moderate (n = 32), and severe (n = 17). Median activity of SOD and glutathione peroxidase was lowest in the severe stage of endometriosis, whereas the median activity of lipid peroxide was highest in the severe stage of endometriosis in both blood and peritoneal fluid samples. There was a statistically significant increase in oxidative stress with the severity of endometriosis. Conclusions: Oxidative stress might play a role in the disease process of endometriosis. Control of oxidative stress can be used as the latest treatment option for the management of endometriosis.